Like” and “Love” Responses as Addiction Factors on Social Media - Mega Putri Alifa; Miskatyas Putri Aransih; Diah Ayu Aguspa Dita; Rizki Edmi Edison (Fakultas Ilmu Pendidikan)
The discovery of internet has facilitated humans in their daily life such as in getting information, performed business transaction, etc. The occurence of social media since the 1990s has developed a new function of internet which enables the users to interact with each other virtually. Unfortunately, social media is suspected to cause phubbing behavior among internet users. A previous study has stated that the ‘like’ and ‘love’ responses in social media posts may cause a social media addiction in the users’ everyday life that can interfere with their daily activities. In this article, we explain briefly a review from neuroscience perspective on the emergence of addictive behavior in the use of social media in daily life.